The Impact of Import Competition from China on the Skill-Bias of Manufacturing Employment across South African Regions between 2001 and 2011 - Matumba, Diana Mukovhe (School of Economics, 2020)
South Africa and China established their first official diplomatic ties in 1998. A decade later in 2008 China had become South Africa’s largest bilateral trade partner which presents both complementary and competitive outcomes for the South African labour market. This study explores the competitive outcomes, particularly the impact that China has had on the skill bias of manufacturing employment within South Africa’s local municipalities between 2001 and 2011. The study follows on from two theories of trade: the Heckscher-Ohlin theory with its Stopler-Samuelson theorem, and specific factor theories. The identification method employed in this study was developed by Autor, Dorn and Hansen (2013) and seeks to exploit variation across South African municipalities which stems from initial differences in industry specialisation and instrumenting for South African imports using changes in Chinese imports by other low- and middle-income countries. The data used in the current study is from the UN Comtrade as well as South African population census data from 1996, 2001 and 2011. This study makes two main contributions to the literature by looking at the impact that import competition has on manufacturing employment in local labour markets, and how this impact varies by skill set and gender. The main finding of the study was that Chinese import exposure was biased against low-skilled workers as it resulted loss of employment for the low-skilled workers, and had a minimal effect on the employment of high-skilled workers.